Q: 49 plus 14x plus 2 equals?

Write your answer...

Submit

Still have questions?

Related questions

(x2 + 14x + 49) = (x + 7)2

49 x2 + 14x = -7 x2 + 14x + 49 = 42 (x + 7)2 = 42 x = -7 ± √42

x2 - 14x = -49 ∴ x2 - 14x + 49 = 0 ∴ (x - 7)2 = 0 ∴ x = 7

x2 - 14x + 49 = (x - 7)2

-14x

4x2 + 28x + 49 = 4x2 + 14x + 14x + 49 = 2x(2x + 7) + 7(2x + 7) = (2x + 7)(2x + 7) or (2x + 7)2

(14x)(x)+1 14x^2 + 1

Re-arranging, x2 - 14x +49 = 0 Factorising, (x-2)(x-2) = 0, hence x=2.

(x - 7) is.

Notice that the left side of the equation is a perfect square (x - 7)2 = x2 -14x + 49. so (x - 7)2 = 4. Take square root of both sides: x - 7 = Â± 2, x = 9, or x = 5.

y=-2/3x with any y-intercept except -2.

It is a quadratic equation and the values of x are -1/2 or -2/3Do you mean 12x2+14x+4 = 0If so then x = -2/3 and x = -1/2